Pengembangan oven dengan kontrol elektronik untuk peningkatan kapasitas dan kualitas produksi kue bolu - Muladi Muladi; Yuni Rahmawati; I Made Wirawan; Samsul Hidayat; Fachur Rozy Dwi Septian; Fiqhy Isrofil (University of Islam Malang, 2021)
Community service with SME Sakinah Bakery is carried out to increase the production capacity and quality. Sakinah Bakery produces sponge cake and pastries that are very popular within the community and spread across 500 vendor shops in Malang City and Regency. Consumer demands has not been fully fulfilled due to low production capacity. About 10% of the product are undercooked or overcooked. These low quality products reduce the taste and aroma, breaks easily and becomes mushy quickly. Based on surveys and interviews, partner needs an large capacity oven that can produce well-cooked biscuits. The production tool that determine the cake ripeness is oven. This problem is overcomed by making an oven with electronic controls to stabilize the temperature and baking time. Temperature control with sensor feedback mounted on the combustion chamber forms a stable closed loop control system. Proper heating is obtained by controlling the LPG main valve. The three furnaces are spread out to get an even heating. The oven was able to increase 60% the production capacity per bake. The number of fail product decreases by 5.19% indicated that the product quality increases. Technology transfer in the form of training is carried out to maintain the quality.